Use of an anisotropic absorber for simulating electromagnetic scattering by a perfectly conducting wire - Skigin, Diana Carina (2003)
A perfectly matched anisotropic absorber (PMAA) is used as a new type of medium in a formalism previously developed for investigating diffraction from an inhomogeneous isotropic aperture in a thick metallic screen. In this paper we consider that the aperture consists of five homogeneous regions: PMAA, transparent dielectric, perfect conductor, transparent dielectric and PMAA. This configuration could allow us to simulate a conducting cylinder of rectangular section in open space and it sets the basis for further extensions of the method to other geometries. We present near and far field simulations for different geometrical and constitutive parameters of the PMAA regions. The results seem to indicate that this new medium could be used to represent a lateral open space, thus enhancing the modal method and making it suitable to simulate scattering problems of finite objects.